A Lindahl solution to international emissions trading - Yukihiro Nishimura (Queen's University, Department of Economics, 2008)
We consider international negotiations on the level of global pollution, and examine the Lindahl solution which determines the distribution of the pollution permits with unanimous agreement. We show various properties to clarify difficulties to achieve a Pareto efficient allocation as an agreement. The Lindahl solution may result in an unfair allocation, and it does not belong to the γ-core as in other solutions based on emissions trading. On the other hand, we provide mechanisms that implement the Lindahl solution as the subgame-perfect equilibrium. We also consider the market with region-specific prices as a device to induce second-best Pareto efficient allocations.
Keywords: D61; D62; D63; D78; H87; Q54; Q58; 330; International emissions trading; Global externality; Lindahl equilibrium; Efficiency; Equity; Core; Implementability; Second-best analysis; Umweltbelastung; Grenzüberschreitende Umweltbelastung; Emissionsrechte; Emissionshandel; Externer Effekt; Second Best; Theorie